2016
DOI: 10.1007/s00383-016-3856-7
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of 3′ UTR of MAMLD1 gene is also associated with increased risk of isolated hypospadias in Indian children: a preliminary report

Abstract: Occurrence of MAMDL1 gene polymorphisms, specially of c.2960C>T in 3' UTR of its exon 7 is associated with a higher risk of IH in Indian children, probably by lowering androgenic levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The mastermind-like domain-containing 1 ( MAMLD1 ) gene, previously known as Chromosome X open reading frame 6 ( CXorf6 ) or F18 (OMIM# 300120), was first identified in two patients with myotubular myopathy and male hypogenitalism, who were found to harbour a deletion on chromosome Xq28 [ 4 , 5 ]. Although MAMLD1 is 70 kilobase long and contains 12 exons, only 7 of them have been validated to date [ 6 ]. Owing to in-frame alternative splicing, exons 3–6 encode two proteins of 701 and 660 amino acids, respectively, depending on whether the transcript includes or excludes exon 4.…”
Section: Introductionmentioning
confidence: 99%
“…The mastermind-like domain-containing 1 ( MAMLD1 ) gene, previously known as Chromosome X open reading frame 6 ( CXorf6 ) or F18 (OMIM# 300120), was first identified in two patients with myotubular myopathy and male hypogenitalism, who were found to harbour a deletion on chromosome Xq28 [ 4 , 5 ]. Although MAMLD1 is 70 kilobase long and contains 12 exons, only 7 of them have been validated to date [ 6 ]. Owing to in-frame alternative splicing, exons 3–6 encode two proteins of 701 and 660 amino acids, respectively, depending on whether the transcript includes or excludes exon 4.…”
Section: Introductionmentioning
confidence: 99%
“…Geller et al, (Geller et al 2014), has been tested on hypospadias cases and control, and identified 18 genomic regions showing independent association with P < 5 × Kappa (DGKK6) which showed differential genetic association with hypospadias risk, positive in Caucasians and negative in the Chinese population. Indian reports have also shown significant association between SRD5A2-V89L (Samtani et al 2011), SRD5A2-A49T, R227Q and TA repeat gene polymorphisms (Samtani et al 2015) and MAMLD1 (c.2960C>T) (Ratan et al 2016) with hypospadias risk and also the severity of the disease. Hence, till date, few genetic associations have been reported in Indian studies but no comprehensive approach has been followed to assess the genetic involvement of different SNPs contributing to pathways like sex hormone biosynthesis and metabolism; embryonic development and Phospholipase D signaling with the severity of Hypospadias.…”
Section: Discussionmentioning
confidence: 92%
“…There are few reports on LH levels in patients with normal testosterone (at different ages), which are as follows: low-normal range LH (1), normal (low range) LH but increased LH after hCG stimulation (1,8), and normal LH (high range) (15). Furthermore, a comparative study of testosterone and LH levels between MAMLD1-hypospadias patients and control individuals of the same age gave statistically significant differences only in the 4-to 8-year-old group and not at lower ages (28).…”
Section: Discussionmentioning
confidence: 96%